The Reflective Teaching Practices using PMRI and Collaborative Learning - Dewi Rawani; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Ely Susanti (Jurnal Pendidikan Matematika, 2023)
This research is aimed to design learning environment in which teacher can create a learning process in develop their reflective practices. Gending Sriwijaya traditional dance, which is familiar with culture in South Sumatera Indonesia, can be as a starting point for context in geometry translation. Applying The Indonesian Realistic Mathematics Learning Approach (PMRI) is one approach that uses contextual. The research used design research consisting of preparation of the experiment, design experiment and retrospective analysis. This research data were collected through classroom observation, documentation, interview, and field notes. The result of this research tries to establish that reflective teaching practice is a tool to makes room for teachers to critically examine any assumptions regarding acceptable objectives, methods, problems and solutions. By reflecting, conducting analysis, and coming to conclusions about what has occurred, the teacher might indirectly learn about the benefits and drawbacks of applying what they have learned. Collaborative learning supports and enhances learning by engaging groups which work together to solve problems, complete tasks, or learn new concepts. Students who have more ability help less-able students. On the other hand, less-able students ask for help from more-able students.